Uncompromising honor - Weber, David, 1952- (Weber, David, 1952- Honor Harrington., 2018)
"The Solarian League's navy counts its superdreadnoughts by the thousands. Not even they know how large their economy is. And for hundreds of years they have borne the banner of human civilization. But the 'Mandarins' who rule today's league are corrupt, venal, accountable to no one and have decided that the Star Kingdom of Manticore must be destroyed. Honor Harrington has worn the Star Kingdom's uniform for over a half a century and now has a seat on the highest military and political councils of the Grand Alliance. Very few people know war they Honor does. Very few have lost as many men and women, as many friends, as much family, as she has. Yet despite that, hers has been a voice of caution. But they have finally killed too many of the people Honor loves. Hers is the voice of caution and compromise no longer and the galaxy is about to see something it has never imagined. The Salamander is coming for the Solarian League and Hell is coming in her wake"--